PENGARUH MODEL PEMBELAJARAN GUIDED DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK KELAS XI MIPA SMAN 14 PADANG - Firna Melisa Nofma (Departemen Matematika, 2022)
Math classes allow students to develop math skills, including problem solving skills.. But in fact, the mathematical problem solving ability of XI MIPA students at SMAN 14 Padang still low. This can be determined by the first test of mathematical problem solving ability, which determines that the student failed to solve the problem. One effort to overcome these problems is to use the GDL model. The purpose of this study was to analyze that the mathematical problem solving ability of students who studied with the guided discovery learning model was better than the students who studied with the guided discovery learning model, as well as to compare and explain the development of students' mathematical problems. As long as the GDL model is applied in class XI MIPA SMAN 14 Padang, these problems can be resolved. The type of research used is a quasi-experimental research with a non-equivalent posttest-only control group design. The population of class XI MIPA SMAN 14 Padang in the academic year 2022/2023. The sample was obtained using the Simple Random Sampling technique so that class XI MIPA 2 was chosen as the experimental class and XI MIPA 4 was the control class. The tools used are quizzes at each meeting to check the development of students' mathematical problem solving abilities in the lab class, and essay-style math problem solving skills to compare their mathematical problem solving abilities. Student skills in the experimental and control classes. According to data analysis from quizzes, each math problem solving index increases. The value of P = 0 was obtained based on the results of the analysis of the mathematical problem solving ability test. The P value is smaller than = 0.05, which means that the application of the GDL model has an effect on students' mathematical problem solving abilities, and the mathematical performance of students who use (GDL). Keywords - Guided Discovery Learning (GDL), Problem Solving